The design of a high aspect ratio HALE aircraft composite wing. part II: buckling and flutter speed analysis / Bambang K. Hadi and IndraPermana - Hadi, Bambang K.; Permana, Indra (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
This is the second part on the design of a high aspect ratio HALE-UAV wing using composite materials. The first paper deals only with the static strength analysis. This paper is a continuation of the first paper and presents buckling and flutters analysis. The wing was made of a carbon/epoxy laminate with orthotropic arrangement, [0°/0°/45°/-45°]ѕ. Buckling phenomenon was evaluated only at the upper wing box skin panel and used linear analytical equation to determine the critical buckling load in each skin panel. The results showed that the upper wing skin was not safe from buckling and it needs structural thickness improvement. Flutter analysis was then performed on this configuration by using numerical approach based on finite element structural models and doublet lattice method. This analysis used finite element software and implemented p-k method to compute the flutter conditions. It was found that the designed wing structure has high flutter speed and it was safe from flutter phenomenon.